Growing old before becoming rich challenges of an aging population in Sri Lanka. ([Manila] Asian Development Bank, 2019)
Discusses how Sri Lanka can prepare for the challenges of an aging population. This publication analyzes the living arrangements and incomes of the over 60s in Sri Lanka, and patterns and trends of aging. It identifies the challenges the country is likely to face and suggests how policy makers can tackle them.
Keywords: Aged -- Care and hygiene -- Sri Lanka; Social rights -- Sri Lanka; Electronic books